Statistical analysis of Municipal Solid Wastes Generation: A Case Study of Selected ULB’s of Andhra Pradesh - et al., S.A. Shahanaz Begum (International Journal of Advanced Science and Technology, 2019)
It is very essential to identify the quantification of generation of solid wastes for its treatment and effective way of handling. This paper mainly focused to elevate the scenario of current solid waste generation and tried to bridge the gap in MSWMS in 10 selected urban local bodies with the possible remedies. In the present study, an attempt is made to find the correlation in physio chemical parameters of MSW, between town to town with respect to the solid waste generation and parameter to parameter by means of correlation matrix. The results of present study help to establish common waste management practices which supports in effective prediction. This study further recommends an integrated solid waste management model.